1986
DOI: 10.1007/bf02386831
|View full text |Cite
|
Sign up to set email alerts
|

Congenital absence of the portal vein in oculoauriculovertebral dysplasia (Goldenhar syndrome)

Abstract: Absence of the portal vein with systemic visceral venous return was demonstrated in an 8-year old girl with oculoauriculovertebral dysplasia (Goldenhar syndrome) during preoperative evaluation of a liver mass. Congenital absence of the portal vein is a rare malformation of potential clinical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 6 publications
1
60
0
Order By: Relevance
“…In addition, the girl had macrostomia and bilateral ear tags and pits, as in OAV defect. We are not aware of other examples of OAV defect with vena cava anomalies, although a case with congenital absence of the portal vein has been reported [Morse et al, 1986]. Our findings support the hypothesis that OAV defect may be part of a malformation complex involving organization of asymmetric structures.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, the girl had macrostomia and bilateral ear tags and pits, as in OAV defect. We are not aware of other examples of OAV defect with vena cava anomalies, although a case with congenital absence of the portal vein has been reported [Morse et al, 1986]. Our findings support the hypothesis that OAV defect may be part of a malformation complex involving organization of asymmetric structures.…”
Section: Discussionsupporting
confidence: 87%
“…This anomaly has been reported mostly as a congenital absence of the portal vein in association with liver tumors and other congenital anomalies [1][2][3][4][5][6][7][8][9][10]. In this report, we present the case of a patient with congenital extrahepatic portocaval shunt in association with Dubin-Johnson syndrome who developed hyperplastic nodules in the liver.…”
mentioning
confidence: 87%
“…Morse et al reported a patient with CAPV who underwent liver transplantation for hepatoblastoma that was initially diagnosed FNH 2 years previously (6,7). This suggests that long-term follow-up and monitoring for malignancy should be mandatory, even with an initial diagnosis of benign tumor.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only 35 cases of CAPV have been reported in the literature (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). The age at diagnosis ranges from 1 day to 64 years.…”
Section: Introductionmentioning
confidence: 99%